Case Studies in Elementary and Secondary Curriculum: SAGE Publications - Boboc, Marius J; Nordgren, R. (Rollin) D (SAGE Publications, Incorporated, 2009)
This book provides 21 real-life cases that give the opportunity for educators to explore different perspectives of the issue of curriculum.